Ibn e- Oqdeh’s Biography; Contrasting Ottoman and Alawite s’ Biography, A Case Study of Prophetic Era - Mohammadrez Hedayatpanah; Ali Ahmadi (تاریخ اسلام)
Abu Abbas Ahmad ibn e- Mohammad ibn e- Saeed ibn e- Oqdeh (333 A.H) is considered as one of the Zeidi-Jarudi scholars of hadith in the third and fourth centuries and the author of more than thirty books. Like ibn e- Helal e- Thaqafi (283 A.H), Nasr ibn e- Mozahem (212 A.H), Mohammad ibn e- Omar e- Joa’ee (355 A.H), he is also the agent of Alawites’ historiography which is against Ottoman historiography. This article is to investigate the conduct of Prophet Mohammad (PBUH) with the emphasis on the historical narrations by Ibn e- Oqdeh and their comparing with Prophetic conduct reported by Othman trend with a historical-narrative approach. After the critical analysis of the documents of both trends, it is concluded that the view of Ibn e- Oqdeh is to foreground the highest position of Amir al- Momenin Ali (PBUH) and the Prophet’s household in the events occurred in the era of Prophet Mohammad (PBUH) and this issue differentiates Ottoman and Alawites’ trends.